Pengembangan Panduan Sosiodrama dengan Nilai-Nilai Serat Sasana Sunu untuk Meningkatkan Perilaku Sopan Siswa Muslim - Arilla Ainda Ubak; Widya Multisari; Ella Faridati Zen; Siti Syazwani Zulkuple (State Islamic University (UIN) Salatiga, 2025)
The decline in manners has become an increasingly concerning issue impacting student development, which, if left unaddressed, may adversely affect their future prospects. This developmental study aims to produce a sociodrama guidebook incorporating the values of Serat Sasana Sunu to enhance students’ polite behavior, ensuring its acceptability through expert evaluations and feedback from prospective users. The research employed the Borg and Gall development model, proceeding through the first five stages tailored to the study’s requirements. Results indicate that the guidebook received an average rating of 3.2 from material experts, categorized as feasible; 3.58 from media experts, deemed very feasible; and 3.98 from prospective users, also classified as very feasible. Based on these assessments, the guidebook is concluded to be highly suitable for implementation (mean score = 3.58). This development contributes by enriching service materials aligned with student needs and offers an innovative intervention by integrating local cultural elements. Nevertheless, the study’s limitations include its confinement to initial trials and product revisions. Future research is recommended to evaluate the guidebook’s effectiveness comprehensively.